Research for effective social work practice - Krysik, Judy.; Finn, Jerry (New York, NY : Routledge, 2010)
Very often research texts for social work students are dry, boring, and hard to relate to. Not this book! Nor do authors Krysik and Finn shy away from teaching research skills that are actually interesting and useful to students interested in real-life social work practice.
The context of social work research -- The politics and ethics of social work research -- The research process : from problems to research questions -- Single subject research -- Qualitative research -- Group research design -- Sampling -- Measurement -- Implementation : from data collection to data entry -- Describing quantitative data -- Bivariate statistics and statistical inference -- Evaluation of social work services -- Writing and presenting research.
Includes bibliographical references and index.
Keywords: Social service -- Research; Social service -- Methodology; Social workers -- Professional ethics; Qualitative research -- Moral and ethical aspects; Group work in research; Sampling (Statistics)